Ethnobotany of Kepuh (Sterculia foetida L.) Samawa Ethnic Communities in Sumbawa Regency, West Nusa Tenggara - Arya Arismaya Metananda; Ervizal AM Zuhud; Agus Hikmat; Nurul Qomar; Defri Yoza; Niskan Walid Masruri; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2022)
Kepuh is multipurpose plant which began endangered. Information on ethnobotanical studies or knowledge and use of this species is still limited. This research is structured to answer this problem. By using the method of interviewing community leaders in Sumbawa, this study found that local wisdom related to kepuh is quite diverse. Good knowledge as well as the use of kepuh found among others for food, medicine, bio-fuel, jewelry, building materials, traditional ceremonies, handicrafts, traditional games, and environmental services. Information on the benefits of kepuh should be disseminated. It is hoped that the ethnobotanical study of kepuh can be a good start to support kepuh conservation in the future.